Change in the Distance From the Axillary Nerve to the Glenohumeral Joint With Shoulder External Rotation or Abduction Position. (July 2017) - Simone, Juan Pablo; Streubel, Philipp N.; Sanchez-Sotelo, Joaquin; Steinmann, Scott P.; Adams, Julie E.
Background: This study investigated whether axillary nerve (AN) distance to the inferior border of the humeral head and inferior glenoid would change while placing the glenohumeral joint in different degrees of external rotation and abduction.Methods: A standard deltopectoral approach was performed on 10 fresh-frozen cadaveric specimens. The distance between AN and the inferior border of the humeral head and inferior glenoid while placing the shoulder in 0°, 45°, and 90° of external rotation or abduction was measured. Continuous variables for changes in AN position were compared with paired 2-tailed Student t test.Results: The mean distance between the AN and the humeral head with the shoulder in 0°, 45°, and 90° of external rotation and 0° of abduction was 13.77 mm (SD 4.31), 13.99 mm (SD 4.12), and 16.28 mm (SD 5.40), respectively. The mean distance between the AN and glenoid with the shoulder in 0°, 45°, and 90° of external rotation was 16.33 mm (SD 3.60), 15.60 mm (SD 4.19), and 16.43 (SD 5.35), respectively. The mean distance between the AN and the humeral head with the shoulder in 0°, 45°, and 90° of abduction and 0° of external rotation was 13.76 mm (SD 4.31), 10.68 mm (SD 4.19), and 3.81 mm (SD 3.08), respectively. The mean distance between the AN and glenoid with the shoulder in 0°, 45°, and 90° of abduction was 16.33 mm (SD 3.60), 17.66 mm (SD 5.80), and 12.44 mm (SD 5.57), respectively.Conclusions: The AN position relative to the inferior aspect of the glenohumeral joint does not significantly change despite position of external rotation. Increasing shoulder abduction over 45° decreases the distance from the glenohumeral joint to the AN and should be avoided.